Garden at rear - Ghosh, Ayan (2023)
The V-shaped plot allotted for the BMC building considerably limited the kind of freedom Frederick Stevens had while designing CSMT and his earlier projects, where the plots were larger and symmetrical. To maximize the available space, Stevens pushed the building to the edge of the plot, which opened enough space at the rear that he used as a garden.